Transparent antenna design for wireless access point application - Azini, A. S. (2013)
In this paper, transparent monopole antenna using AgHT-4 ﬁlm has been presented. The radiating element and ground plane are both designed using AgHT-4 while the substrate is made of glass. By having a suitable arc-shape slot on the ground plane, a wide impedance bandwidth of 41.89% (2.00GHz to 3.06GHz) that cover WLAN system in the 2.4GHz has been obtained. The transparent antenna provides gain of 3.16dBi.